2010
DOI: 10.1111/j.1600-6143.2010.03274.x
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation for Neonates Using Segment 2 Monosubsegment Graft

Abstract: The prognosis of liver transplantation for neonates with fulminant hepatic failure (FHF) continues to be extremely poor, especially in patients whose body weight is less than 3 kg. To address this problem, we have developed a safe living donor liver transplantation (LDLT) modality for neonates. We performed LDLTs with segment 2 monosubsegment (S2) grafts for three neonatal FHF. The recipient age and body weight at LDLT were 13-27 days, 2.59-2.84 kg, respectively. S2 or reduced S2 grafts (93-98 g) obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 16 publications
0
39
0
2
Order By: Relevance
“…10,11,17,[24][25][26] In this regard, to optimize the size of the graft matching the recipient's abdominal cavity, it has been suggested that for recipients under 10 kg the GRWR should be < 4%. 10,11,17,[24][25][26] In this regard, to optimize the size of the graft matching the recipient's abdominal cavity, it has been suggested that for recipients under 10 kg the GRWR should be < 4%.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,17,[24][25][26] In this regard, to optimize the size of the graft matching the recipient's abdominal cavity, it has been suggested that for recipients under 10 kg the GRWR should be < 4%. 10,11,17,[24][25][26] In this regard, to optimize the size of the graft matching the recipient's abdominal cavity, it has been suggested that for recipients under 10 kg the GRWR should be < 4%.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the left lateral segment thickness was introduced in neonatal living-donor liver transplant, but this did not improve recipient survival. 9,10 Tailoring the graft size and reducing the thickness of the left lateral segment may enable safe transplant in small children without the associated complications of large-for-size grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The recipient procedure has been described in previous reports [6,7]. As the key part of the recipient operation, we judge whether or not we are able to perform primary abdominal wall closure 3-dimensional computer-generated model of the donor liver was used to analyze the intrahepatic vasculature and to evaluate the graft volume of S2 and S3 following the dominant portal vein branches.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Following previous reports, we attempted to transplant the S3 graft in small infants. Even though the size of the graft was reduced adequately, the thickness of the graft was not satisfactory for placement in the recipient.We developed a safe LDLT technique for neonates by modifying the previous method, using an anatomical graft or so-called "Segment 2 monosegment graft" (S2 graft) [6]. We believe that the S2 graft enables reduction of not only LLS…”
mentioning
confidence: 99%
See 1 more Smart Citation